Low Impact Aerobic On Blood Glucose Levels And Peripheral Circulation In Type II Diabetes Mellitus Clients In 2022 - Darma, Dimas Dewa; Sudirman, Sudirman; Widiyanto, Budi (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Hysical activities carried out, such as Low Impact Aerobics in patients with type II diabetes mellitus, can increase insulin resistance sensitivity to optimize insulin function. The purpose of this study was to determine the impact of low aerobics on blood glucose levels and peripheral circulation in type II diabetes mellitus clients. This research design uses true experimental with pre-test and post-test control group design. The total sample of 36 people consisted of 12 intervention group 1, 12 people in intervention group 2, and 12 people in the control group . The activity was carried out at the UPT Puskesmas working area of Semarang City in 2022. The sampling technique uses simple random sampling. Data analysis using Wilcoxon and Wallis crucible was α < 5%. The results showed that the average value of blood sugar levels after being given alow-impact. Aerobic intervention decreased by 57 mg/dl with p-value = 0.004. The mean peripheral circulation value of ABI after low impact aerobic intervention increased by 0.09 mmHg with p-value = 0.002. After the low impact aerobic intervention, the average CRT value of peripheral circulation decreased by 0.67 mmHg with p-value = 0.011. In conclusion, e fek eerobic has a low impact in lowering blood glucose levels and improving peripheral circulation.